A case report of neonatal coronavirus disease-19 infection in South India - Phadke, Abhishek K; Kumble, Ali; Varghese, Arun; Sherigar, Bhavana; Reddy, Rishitha (Indian Journal of Case Reports, 2020)
The global pandemic of coronavirus disease 2019 (COVID-19) has affected a significant population across all ages around the globe. In spite of the significant number of case reports on neonatal COVID-19 published across the world, there is a paucity of data on cases reported from India. We report a case of neonatal COVID-19 infection from Mangalore in South India. A term neonate was born to a 33-year-old nasopharyngeal swab real-time reverse transcriptase-polymerase chain reaction (rRT-PCR) severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) (novel corona) virus-positive mother by emergency cesarean section. The baby was shortly handed over to the patient’s bystander, who was tested 1 day before be rRT-PCR novel coronavirus negative and was kept in an isolation room nearby. The pharyngeal swab of the neonate tested at 48 h of life for rRT-PCR coronavirus was reported as positive. Following this, the baby was roomed-in with the mother to an isolation room and direct breastfeeding was initiated. No further investigations were done and the baby was discharged along with the mother on the 14th postnatal day. Whether the case is vertical transmission from mother to newborn, could not be ascertained. We had not done an rRT-PCR SARS-CoV-2 virus detection of cord blood and placenta in this case for supporting the diagnosis of intrauterine transmission, but the possibility of vertical intrauterine transmission is not ruled out.